Development and use of recombinant gonadotropin-releasing hormone vaccines to sterilize cattle: a review - Greer, J.; Rozell, Timothy G. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
A possible alternative to conventional castration methods is the use of vaccines that can be injected in order to sterilize animals. One promising approach involves the use of a vaccine that causes cattle to produce an immune response against one of their own reproductive hormones, gonadotropin releasing hormone (GnRH). Immunization against GnRH results in a decrease in the amount of GnRH circulating within the animal's blood. Therefore, follicle stimulating hormone (FSH) and luteinizing hormone (LH) are not stimulated to be released, and, subsequently their levels required for reproductive function. Experimentation has shown that immunization against GnRH can effectively block reproductive function in an age-independent manner but has little effect on carcass and growth parameters. However, about 10% of cattle tested do not respond when immunized against GnRH, regardless of dosing regimen. Further research is needed to improve the efficiency of potential GnRH immunocastration vaccines.
Keywords: Gonadotropin releasing hormone; Follicle stimulating hormone; Luteinizing hormone; Antibody; Immunization